The cold dark matter model with cosmological constant and the flatness constraint - A.C.B. Antunes (Brazilian Journal of Physics, 2010)
The Hubble parameter, a function of the cosmological redshift, is derived from the Friedmann-Robertson-Walker equation. The three physical parameters H0, Ω0m and ΩΛ are determined fitting the Hubble parameter to the data from measurements of redshift and luminosity distances of type-Ia supernovae. The best fit is not consistent with the flatness constraint (k = 0). On the other hand, the flatness constraint is imposed on the Hubble parameter and the physical parameters used are the published values of the standard model of cosmology. The result is shown to be inconsistent with the data from type-Ia supernovae.